STUDI LITERATUR: PERAN GURU KELAS DALAM MENGATASI KESULITAN BELAJAR ANAK SLOW LEARNER DI SEKOLAH DASAR - Hasnah Fadiyah; Putri Khoirunnisa; Rahmalia Intan Bardilah; Rahmi Tri Handayani (STKIP Subang, 2024)
The aim of this research is to see the influence of teachers' efforts in overcoming the learning difficulties of slow learner students. The research method used is a qualitative research method with data sources obtained from several national journals from the past 10 years. The study carried out used a narrative review model by comparing data from several journals which had been analyzed and summarized based on existing theories and models. The findings of this research state that teachers have a very important role in dealing with slow learner students. Because the teacher's role is most influential in increasing student learning success to assist in the learning process. If in learning the teacher's role in helping slow learner students is not paid attention to, there will be no success in learning for slow learner students because the class teacher plays the role of guide, companion, mediator and evaluator.